The Political Economy of Bread and Circuses: Weather Shocks and Classic Maya Monument Construction - Melissa Rubio-Ramos; Christian Isendahl; Ola Olsson (CESifo GmbH, 2024)
In early states, government elites provided both productivity-enhancing infrastructure, such as irrigation systems, as well as seemingly non-productive monumental architecture like temples and pyramids. The nature of this "bread-and-circuses"-tradeoff is not well understood. In this paper, we examine this phenomenon in the Classic Maya civilization (c. 250-950 CE) where city-state elites chose between investing in essential water management infrastructure (reservoirs, canals), and monumental architecture. We analyze information from 870 dated monuments from 110 cities. Correlating this dataset with a proxy record for variations in annual rainfall, we find–perhaps counter-intuitively–that monumental construction activity was more intense during drought years. A text analysis of 2.2 million words from deciphered hieroglyphic inscriptions on monuments, further shows higher frequencies of terms associated with war or violent conflict during periods of drought. We propose that in the Classic Maya setting, with numerous small city-states, monument construction functioned as a costly signalling device about state capacity, designed to attract labor for future control of revenue.
Keywords: 330; bread and circuses; public goods; monumental architecture; drought; Maya